A novel host material with high thermal stability for green electrophosphorescent device. Issue 11 (17th March 2016) - Liang, Wenqing; Gao, Zhixiang; Song, Wenxuan; Su, Jianhua; Guo, Kunpeng; Dong, Qingchen; Huang, Jinhai; Wong, Wai-Yeung
Abstract: A new bipolar host material based on triphenylamine, fluorene and 1, 2-diphenyl-1 H -benzo[ d ]imidazole moieties, N, N -diphenyl-4-(9-phenyl-2-(4-(1-phenyl-1 H -benzo[ d ]imidazol-2-yl)phenyl)-9 H -fluoren-9-yl)aniline (DPPBIPFA), was designed and synthesized. The as-synthesized material was well characterized by 1 H and 13 C NMR spectroscopy, high-resolution mass spectrometry and thermogravimetric analysis, respectively. The photophysical and electrochemical properties of the material were also studied. The material exhibited an excellent thermal stability ( T d = 475 °C), electrochemical stability and high triplet energy (2.68 eV). A green phosphorescent organic light-emitting diode (PhOLED) device based on DPPBIPFA as the host material and Ir(ppy)3 as the dopant was fabricated, which displayed favorable electrophosphorescent properties with a turn-on voltage of 3.75 V, a maximum brightness of 1685 cd/m 2 and a maximum current efficiency of 4.26 cd/A. Graphical abstract: A new bipolar host material based on triphenylamine, fluorene and 1, 2-diphenyl-1 H -benzo[ d ]imidazole moieties, N, N -diphenyl-4-(9-phenyl-2-(4-(1-phenyl-1 H -benzo[ d ]imidazol-2-yl)phenyl)-9 H -fluoren-9-yl)aniline (DPPBIPFA) was designed and synthesized via Suzuki coupling. The material exhibited an excellent thermal stability ( T d =475 °C), electrochemical stability and high triplet energy (2.68 eV), which can be used as bipolar host in OLEDs.